Academic Senate Minutes 2009-12-03 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes delayed. Associated Students Report. Vice President of SAEM Report. By-Laws Revision: Change to Charge of SAC approved. Provost Report. Resolution to form a Senate Diversity Committee – First Reading. Discussion Item: Statewide Senate Resolution designating March 2nd as the Day without the CSU. Discussion of Budget Prioritization Process. Special Report: Student Retention Task Force.